Empagliflozin preserves skeletal muscle function in a HFpEF rat model - Winzer, Ephraim Bernhard; Schauer, Antje; Langner, Erik; Augstein, Antje; Goto, Keita; Männel, Anita; Barthel, Peggy; Jannasch, Anett; Labeit, Siegfried; Mangner, Norman; Linke, Axel; Adams, Volker (International journal of molecular sciences, 2022)
Besides structural alterations in the myocardium, heart failure with preserved ejection fraction (HFpEF) is also associated with molecular and physiological alterations of the peripheral skeletal muscles (SKM) contributing to exercise intolerance often seen in HFpEF patients. Recently, the use of Sodium-Glucose-Transporter 2 inhibitors (SGLT2i) in clinical studies provided evidence for a significant reduction in the combined risk of cardiovascular death or hospitalization for HFpEF. The present study aimed to further elucidate the impact of Empagliflozin (Empa) on: (1) SKM function and metabolism and (2) mitochondrial function in an established HFpEF rat model. At the age of 24 weeks, obese ZSF1 rats were randomized either receiving standard care or Empa in the drinking water. ZSF1 lean animals served as healthy controls. After 8 weeks of treatment, echocardiography and SKM contractility were performed. Mitochondrial function was assessed in saponin skinned fibers and SKM tissue was snap frozen for molecular analyses. HFpEF was evident in the obese animals when compared to lean—increased E/é and preserved left ventricular ejection fraction. Empa treatment significantly improved E/é and resulted in improved SKM contractility with reduced intramuscular lipid content. Better mitochondrial function (mainly in complex IV) with only minor modulation of atrophy-related proteins was seen after Empa treatment. The results clearly documented a beneficial effect of Empa on SKM function in the present HFpEF model. These effects were accompanied by positive effects on mitochondrial function possibly modulating SKM function.